The Influence of Perceived Accounting Information System Quality, Ease of Use, and Trust on The Decision To Use E-Wallets in Financial Transactions - Wulan Rachmawati; Erawati Ni Made Adi (Digital Innovation : International Journal of Management, 2025)
In the ever-evolving digital era, digital payment technology has increasingly become the preferred method for conducting financial transactions. This study aims to empirically examine the influence of perceived quality of accounting information systems, ease of use, and trust on the decision to use e-wallets in financial transactions. The sampling method employed in this study was non-probability sampling, specifically purposive sampling, with criteria set for selecting respondents, namely active accounting students from the 2021 cohort who are currently using or have previously used e-wallets for financial transactions. This research is grounded in the Technology Acceptance Model (TAM) and the Theory of Planned Behavior (TPB). Data were collected through a Google Form, yielding 252 valid responses. The data were then analyzed using SPSS Statistics 26. The results show that perceived quality of accounting information systems, ease of use, and trust have a positive influence on the decision to use e-wallets. This indicates that the higher the perceived quality of accounting information systems, ease of use, and trust felt by students in using e-wallets, the more likely they are to decide to use e-wallets in their financial transactions.